2019
DOI: 10.1515/jpem-2018-0324
|View full text |Cite
|
Sign up to set email alerts
|

Frequency, clinical characteristics, biochemical findings and outcomes of DKA at the onset of type-1 DM in young children and adolescents living in a developing country – an experience from a pediatric emergency department

Abstract: Background As per the International Society for Pediatrics and Adolescent Diabetes (ISPAD) census, diabetic ketoacidosis (DKA) is the most frequent cause of diabetes-related death. In developing countries, DKA-related mortality rate ranges from 6% to 24% (Onyiriuka AN, Ifebi E. Ketoacidosis at diagnosis of type 1 diabetes in children and adolescents: frequency and clinical characteristics. J Diabetes Metab Disord 2013;12:47) in contrast to 0.15%–0.31% in the Western world (Poovazhagi V. Risk factors for mortal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
15
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 14 publications
3
15
1
1
Order By: Relevance
“…The dominance of new onset of diabetes of this study might be explained by relatively older age of children who were enrolled in the study. Our results were consistent with the reports from Polish, Pakistanian and Iranian children demostrating the average age groups at the new onset of diabetes 26,29,30 .…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The dominance of new onset of diabetes of this study might be explained by relatively older age of children who were enrolled in the study. Our results were consistent with the reports from Polish, Pakistanian and Iranian children demostrating the average age groups at the new onset of diabetes 26,29,30 .…”
Section: Discussionsupporting
confidence: 93%
“…Other studies report the incidence as 8.6% -67% 25,26 . The significantly wide ranges in the reported incidence might be due to several reasons such as: DKA criteria designed for the study, the prevalence of DM in the index population, the socioeconomic income of the country and racial differences 26,27 . Children less than 2 years of age and adolescents between 10 and 14 years have higher DKA prevalence than other age groups 28 .…”
Section: Discussionmentioning
confidence: 95%
“…There are several reasons for this. It is the most common emergency in pediatric T1DM and is still the major cause of hospitalization, morbidity, and mortality (1,2,9). Most morbidities and deaths due to DKA take place out of the hospital, presumably from φ Appropriate insulin treatment (type/dose): Low-dose intravenous (iv) insulin infusion rate 0.05 U/kg/hr administered for children who is younger than 5 years old, and 0.1 U/kg/h rate used for children older than 5. severe dehydration and acidosis, which can be treated by iv fluids and insulin.…”
Section: Discussionmentioning
confidence: 99%
“…Diabetic ketoacidosis (DKA) is one of the serious acute complications of type 1 diabetes mellitus (T1DM). DKA occurs at the onset of diabetes in half of patients (1,2). The annual rate of DKA in pediatric T1DM is 6-8%, with a case fatality rate ranging from 0.15% to 0.31% in developed countries.…”
Section: Introductionmentioning
confidence: 99%
“…However, the reported rate in the current study is twice the mortality rate from DKA reported in developed countries 6 and within the range reported in developing countries. 38 In Sudan, the poor socioeconomic status and low parental awareness about the risk factors of developing DKA in T1DM patients could contribute to the observed high mortality rate from DKA. 35 Among the limitations of the current study is that biochemical parameters (like blood urea nitrogen and sodium) were not recorded in the majority of the patients' files.…”
Section: Discussionmentioning
confidence: 99%